Microservices - Thones, Johannes (IEEE software, 2015)
In this excerpt from Software Engineering Radio, Johannes Thönes talks with James Lewis, principal consultant at ThoughtWorks, about microservices. They discuss microservices' recent popularity, architectural styles, deployment, size, technical decisions, and consumer-driven contracts. They also compare microservices to service-oriented architecture and wrap up the episode by talking about key figures in the microservice community and standing on the shoulders of giants. The Web extra at http://www.se-radio.net/2014/10/episode-213-james-lewis-on-microservices is an audio recording of Tobias Kaatz speaking with James Lewis, principal consultant at ThoughtWorks, about microservices. They discuss microservices' recent popularity, architectural styles, deployment, size, technical decisions, and consumer-driven contracts. They also compare microservices to service-oriented architecture and wrap up the episode by talking about key figures in the microservice community and standing on the shoulders of giants.